Analisis Perspektif Fraud Pentagon pada Terjadinya Kecurangan Akademik Mahasiswa Akuntansi - Dian Oktarina (Universitas Kadiri, 2021)
The purpose of this research is to show the fraud pentagon perspective on academic cheating in accounting students. The independent variabels in this research are pressure, opportunity, rationalization, capabilities, and personal ethics, while dependent variabel is academic cheating. This research used primary data on online questionnaire. The sample of this research used purposive sampling with criteria of STIE Perbanas Surabaya active accounting students until 2019 and willing to fill out a questionnaire. The research used multiple linear regression. The result is pressure, opportunity, rationalization, and capabilities no effect on cheating academic, while personal ethics negative effect on cheating academic. This is because STIE Perbanas Surabaya has character building activities namely Super Soft skills Mentoring (SSM) which makes the students have good personal ethics, so that minor academic cheating occurs.